Urine thebaine determination by liquid chromatography tandem mass spectrometry after poppy seed consumption. Issue 8 (3rd June 2022) - Bollini, Stephanie Marina; Banks, J. Fred; Hobbs, Gregory A.
Abstract: Laboratories are challenged to distinguish whether a positive urine morphine result is due to heroin use or possible poppy seed consumption. Thebaine is an opium alkaloid that has been shown to be present in the urine of individuals who have consumed poppy seeds, as well as those who have used opium. It is not present in heroin. We present a sensitive, specific liquid chromatography tandem mass spectrometry (LC–MS/MS) assay for thebaine. We show that thebaine is detectable after consumption of two different poppy seed‐containing products for up to 72 h in urine. We discuss limitations of the assay and suggest how the test might best be used. Abstract : A new liquid chromatography tandem mass spectrometry (LC–MS/MS) assay for thebaine is evaluated. It is shown to be sensitive enough to detect thebaine in urine of subjects who have consumed moderate amounts of poppy seeds. Clinical application of the test is suggested.